Pengaruh Model Pembelajaran Take And Give Berbantuan Media Audio Visual Terhadap Hasil Belajar Kelas III - Yuli Yanti; Syifa Fauziah; Nurull Hidayah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2022)
The learning process carried out by educators is varied in using learning models, but student learning outcomes are still low. Based on these problems, the researchers tested the learning process using a learning model that educators had never used, namely the take and give model. This study aims to determine the effect of the take and give learning model assisted by audio-visual media on learning outcomes for class III MIN 10 Bandar Lampung. The type of research used is quantitative research, with a quasi-experimental design (nonequivalent control group design). The place where this research was carried out was at MIN 10 Bandar Lampung. This research was conducted in class III, using two classes as the experimental class and the control class and one class as the validation class. The instruments used to collect data in this study were tests, interviews, and documentation. Data analysis technique using t-test. The results showed that there was an effect of using the take and give learning model assisted by audio-visual media on the learning outcomes of class III MIN 10 Bandar Lampung